2017
DOI: 10.1504/ijmmm.2017.10002091
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multi objective optimisation using TOPSIS method in EDM process with CNT infused copper electrode

Abstract: This paper presents the experimental investigation of the machining characteristics of AISI D2 tool steel on the electrical discharge machining (EDM) process by replacing the copper electrode tool with carbon nanotube (CNT) fused electrode, and checking for improvement in machinability factors like material removal rate (MRR), electrode wear rate (EWR) and surface finish (SR). The problems of high electrode wear in EDM machining, such as poor dimensional and shape accuracy of the machined part, need to be addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In this manner, the compromise ranking Basically the optimal solution is selected and selected The solution is positive and the shortest distance from the ideal solution is negative must also have the greatest distance from the ideal solution. [13] Spatial and temporal characteristics of floods CV-TOPSIS method for disaster risk assessment done In the first part, every year Considered a watchdog for the economy, too Flood risk using CVTOPSIS method 263 observations were examined to obtain scores. [14].…”
Section: Topsis Methods (Similar To Ideal Solution Technique Of Prior...mentioning
confidence: 99%
“…In this manner, the compromise ranking Basically the optimal solution is selected and selected The solution is positive and the shortest distance from the ideal solution is negative must also have the greatest distance from the ideal solution. [13] Spatial and temporal characteristics of floods CV-TOPSIS method for disaster risk assessment done In the first part, every year Considered a watchdog for the economy, too Flood risk using CVTOPSIS method 263 observations were examined to obtain scores. [14].…”
Section: Topsis Methods (Similar To Ideal Solution Technique Of Prior...mentioning
confidence: 99%
“…A stirrer was used to ensure the homogeneity of the powder mixed liquid dielectric in a secondary tank. Circular copper rod of 12 mm diameter was used as the tool, since it is a widely used electrode by the researchers in the EDM process (Raj and Prabhu, 2017). Kumar et al (2016a) Six experiments in all were conducted under the machining conditions stated above.…”
Section: Edm Experiments In the Powder Mixed Dielectric Liquidmentioning
confidence: 99%
“…The research results of each optimization problem depend on the input of each type of problem and the optimization method. Some research results have shown that Deng's method can produce higher multiobjective optimization than Topsis [32,33]. Therefore, it is necessary to have studies to determine the optimal results for each specific problem.…”
Section: Introductionmentioning
confidence: 99%